Audiovisual Narrative for Fashion Heritage: Communicating and Valorizing Archives through Fashion Film - Dorothea Burato (ZoneModa Journal)
The article investigates fashion film as a paratext to the materiality of fashion. It outlines methodology and creative practice in bridging traditional archives with contemporary digital storytelling as a means of knowledge transfer. These may include clothes, design practices, cultural narratives, and brand identities—all tangible and intangible assets that fashion heritage encompasses. Although previous scholarship has commented on the marketing and the aesthetic of fashion films, there is yet to be a comprehensive analysis of their potential as a viable mobility for documenting and communicating fashion’s historical and cultural legacies. The research illustrates how documentary fashion films archive creative processes and brand histories by unpacking a series of case studies. It highlights the role of fashion film festivals as platforms that amplify heritage narratives while fostering discussions on sustainability, diversity, and innovation. The study further proposes the development of a dedicated online database for fashion films, offering a participatory and accessible resource to preserve and disseminate fashion heritage. The article aims to add to the discussion surrounding fashion archival and preservation by providing an argument for fashion films — as aesthetic devices in representing culture and as integral storytelling and archiving tools that can preserve identity from one generation to another.